An Examination of the Relationship between Service Quality Perception of Alternate Banking Delivery Channels and Customer Satisfaction; A Step Forward towards Green Economy: Empirical Evidences from Pakistani Islamic & Conventional Commercial Banks (KASBIT Business Journal, 2019)
This study examines the influence of service quality perception of alternate banking delivery channels offered by renowned Pakistani commercial banks on customer satisfaction as the trend of creating ease with the technological gadgets in every industry, whether service or manufacturing is getting pace over the years. The study evaluates the feedbacks and results to further expand the investments and enrich quality dimensions in order to enhance satisfaction. The nature of research is quantitative and the questionnaire is developed based on the existing literature. Self-administered survey was conducted to collect primary data. Correlation and multiple regressions were used to examine the relationship between variables. Findings of this research revealed that there is a significant positive relationship among the variables, such as tangibles, reliability, compliance, responsiveness, assurance and empathy and they are found strong determinants of service quality that ultimately influence customer satisfaction. The increased preference of adding alternate banking products along with the traditional methods of branch banking is gaining popularity and is also becoming a major marketing tool for most of the commercial banks irrespective of their dual nature e.g. Islamic or conventional. This research has attempted to deliver a better understanding of how the Alternate banking products are captivating the market share to keep up the pace in 21st century coinciding with technological revolution, and to adhere the customer satisfaction- the ultimate prosperity ladder. Fewer studies have been conducted worldwide and yet no empirical analysis found on Pakistan till date. The findings of this research will provide guidance to help policy makers of commercial banks in designing their Alternate banking delivery channels strategies and extend their focus towards customer satisfaction and to become a major contributor towards green economy as it saves tons of paper usage in record handling, filling and reporting.
Keywords: ABDC; all commercial banks; Pakistan